The Effect of Work Experience and Work Ability on the Work Achievement of Civil Servants at the Youth and Sports Education Office (Disppora) Waropen District - Kristian Alberth Worisio; Elizabethh Tuhumury; Eleazar Tfuakani (Budapest International Research and Critics University, 2022)
In relation to the quality of human resources in government and private organizations, in addition to the input factors above, a monitoring and evaluation process is also needed that refers to the work performance appraisal system and mechanism, which is expected to have positive implications in motivating employee performance. Employee performance appraisal itself is closely related to various components of Human Resources both from within the employee himself or from his work environment. Two of a number of components of Human Resources require professional human resources in the field of work at the Department of Education, Youth and Sports (Disppora) of Waropen Regency. The research method is qualitative.